2008
DOI: 10.1179/102453308x316121
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trisomy 12, retinoblastoma gene and P53 in prognosis of B-cell chronic lymphocytic leukemia

Abstract: Interphase and metaphase FISH studies improve the cytogenetic diagnosis of chromosomal abnormalities in B-CLL. Lymphocytosis and trisomy 12 may be a good indicator of poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…1213 The frequency of trisomy 12 positive patients in the EFC6663 study is in line this (8 of the 62 (13%)). Although small in number, all eight of the patients on study experienced clinical benefit (7 PR, 1 SD) and whether this extends to a larger patient population needs to be explored.…”
supporting
confidence: 74%
“…1213 The frequency of trisomy 12 positive patients in the EFC6663 study is in line this (8 of the 62 (13%)). Although small in number, all eight of the patients on study experienced clinical benefit (7 PR, 1 SD) and whether this extends to a larger patient population needs to be explored.…”
supporting
confidence: 74%
“…The Chromosome 12 is considered as a marker of poor prognosis in B-CLL patients [ 16 ], but it was never correlated with myeloma development. Elnenaei and collaborators [ 17 ] reported this cytogenetic alteration in 8% of their myeloma patients, but with no informative data about previous hematological disorder, such as B-CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, CLL patients with deletions of chromosomes 11 or 17 typically show an aggressive disease, with high risk of relapse, drug resistance development, and a median overall survival of 79 and 32 mo, respectively ( 3 ). Finally, T12 CLLs show atypical morphological/immunophenotypic features and the most variable prognosis ( 11 ), with an overall survival spanning between 9.5 and 15.6 y ( 3 , 12 ). It was previously shown that NOTCH1 mutations are prevalent in T12 CLL and are associated with unfavorable prognosis ( 13 , 14 ).…”
mentioning
confidence: 99%